Silica aerogel felt, preparation method thereof and thermal insulation material

By introducing alkenyl groups and fibers into the silica aerogel felt and irradiated crosslinking with acrylates to form an additional crosslinking network, the problem of the easy powder loss of traditional silica aerogel felt is solved, and its mechanical properties and powder loss resistance are significantly improved.

CN119822785APending Publication Date: 2025-04-15GUANGDONG ALISON HI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150344.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional silica aerogel felt tends to lose powder, affecting its performance and reliability in thermal insulation materials applications.

Method used

By preparing an aerogel slurry containing alkenyl group silica aerogel and fibers, pressing is carried out to form an aerogel felt preform and mixed with alkenyl group acrylate for irradiation crosslinking to form an additional crosslinking network, thereby improving the structural strength of the material and anti-powder loss performance.

Benefits of technology

This method effectively improves the mechanical properties and powder-resistance resistance of silica aerogel felt, and improves its reliability and performance stability in thermal insulation materials applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a silicon dioxide aerogel felt, a preparation method thereof and a thermal insulation material. The preparation method of the silicon dioxide aerogel felt comprises the following steps: obtaining aerogel slurry containing silicon dioxide aerogel and fibers; pressing the aerogel slurry to form an aerogel felt prefabricated body; mixing the aerogel felt preform with acrylate, and performing irradiation crosslinking and drying to form a silicon dioxide aerogel felt; wherein the silicon dioxide aerogel contains an alkenyl group. According to the preparation method of the silicon oxide aerogel felt, silicon dioxide aerogel containing alkenyl and fibers are mixed to form an aerogel felt preform, the aerogel felt preform and acrylate containing alkenyl are subjected to irradiation crosslinking together, an additional crosslinking network is formed through chemical crosslinking, and after drying, the silicon dioxide aerogel felt not prone to powder falling can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aerogel materials, and in particular to a silica aerogel felt and a preparation method thereof, and a thermal insulation material. Background Art

[0002] Silica aerogel is a nanoporous material with high porosity, high specific surface area, low light refractive index, low sound propagation velocity, low thermal conductivity, non-flammability and high temperature resistance. Due to these characteristics, silica aerogel is widely used in high and low temperature insulation, space field, catalyst carrier and other fields.

[0003] At present, the mechanical properties of silica aerogel materials are often improved by preparing aerogel felt containing fiber phase. However, the introduction of fiber phase can only improve the performance of silica aerogel materials to a certain extent, and silica aerogel felt still has the problem of local powder loss. Summary of the invention

[0004] Based on this, it is necessary to provide a silica aerogel felt and a preparation method thereof, and a thermal insulation material to improve the problem that traditional silica aerogel felt is prone to powder shedding.

[0005] A method for preparing a silica aerogel felt comprises the following steps:

[0006] obtaining an aerogel slurry containing silica aerogel and fibers;

[0007] Pressing the aerogel slurry to form an aerogel felt preform;

[0008] The aerogel felt preform is mixed with acrylate, irradiated and cross-linked together, and dried to form a silica aerogel felt;

[0009] Wherein, the silica aerogel contains alkenyl groups.

[0010] In some embodiments, the aerogel slurry comprises, by mass percentage:

[0011] Organic solvent 40%~80%,

[0012] Silica aerogel 10%~40%, and

[0013] Fiber 5%~40%.

[0014] In some of the embodiments, the aerogel slurry further comprises 1% to 5% of a dispersant, based on the mass percentage of the aerogel slurry.

[0015] In some embodiments, the fiber comprises one or more of glass fiber, ceramic fiber and carbon fiber; and / or

[0016] The organic solvent includes one or more of cyclohexane, toluene, n-hexane and isooctane.

[0017] In some embodiments, the radiation dose of the radiation cross-linking is 80 kGy~800 kGy.

[0018] In some embodiments, the acrylate includes one or more of methyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol tetraacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene glycol dimethacrylate and trimethylolpropane triacrylate.

[0019] In some embodiments, the method for preparing the silica aerogel comprises:

[0020] The silica wet gel is hydrophobically modified using a modifier and dried;

[0021] The modifier is a silane coupling agent containing an alkenyl group.

[0022] In some embodiments, the modifier includes one or more of vinyltrichlorosilane, 2-propenyltrichlorosilane, 2-butenyltrichlorosilane, 5-hexenyltrichlorosilane, and 7-octenyltrichlorosilane.

[0023] In a second aspect of the present application, a silica aerogel felt is provided.

[0024] A silicon dioxide aerogel felt is prepared by adopting the above-mentioned method for preparing the silicon dioxide aerogel felt.

[0025] In a second aspect of the present application, a thermal insulation material is provided.

[0026] A thermal insulation material comprises the above-mentioned silica aerogel felt.

[0027] The preparation method of the silica aerogel felt uses alkenyl-containing silica aerogel and fibers as initial slurry, and obtains an aerogel felt preform with preliminary shaping and uniformly dispersed fibers by pressing the aerogel slurry. On this basis, the aerogel felt preform is mixed with alkenyl-containing acrylate. Since the aerogel felt preform also contains alkenyl, the aerogel felt preform is chemically cross-linked with the acrylate under irradiation to form an additional cross-linked network. After drying, a silica aerogel felt that is not easy to fall off can be obtained. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0029] In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In this application, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0031] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0033] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0034] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0035] Silica aerogel is a nanoporous material with high porosity. Thanks to its low thermal conductivity and density, silica aerogel is considered to be a highly promising thermal insulation material. However, the connection between silica aerogel particles is relatively fragile, and it has the disadvantage of structural brittleness. When used as a thermal insulation material, it is prone to breakage or powdering, which seriously restricts the promotion and application of silica aerogel materials.

[0036] At present, the mechanical properties of silica aerogel materials are often improved by preparing aerogel felt containing fiber phase. However, the introduction of fiber phase can only improve the performance of silica aerogel materials to a certain extent, and silica aerogel felt still has the problem of local powder loss.

[0037] In view of the above problems, one embodiment of the present application relates to a method for preparing a silica aerogel felt to overcome the problem that traditional silica aerogel felt is prone to powdering.

[0038] The preparation method of silica aerogel felt comprises the following steps:

[0039] obtaining an aerogel slurry containing silica aerogel and fibers;

[0040] Pressing the aerogel slurry to form an aerogel felt preform;

[0041] The aerogel felt preform is mixed with acrylate, irradiated and cross-linked together, and dried to form a silica aerogel felt, wherein the silica aerogel contains olefinic groups.

[0042] The method for preparing silica aerogel felt of the present application selects silica aerogel containing alkenyl groups and fibers as initial slurry, and obtains an aerogel felt preform with preliminary shaping and uniformly dispersed fibers by pressing the aerogel slurry. On this basis, the aerogel felt preform is mixed with acrylate containing alkenyl groups. Since the aerogel felt preform also contains alkenyl groups, the aerogel felt preform is chemically cross-linked with acrylate under irradiation to form an additional cross-linked network. After drying, a silica aerogel felt that is not easy to fall off can be obtained.

[0043] In some embodiments, the aerogel slurry comprises, by mass percentage:

[0044] Organic solvent 40%~80%,

[0045] Silica aerogel 10%~40%, and

[0046] Fiber 5%~40%.

[0047] The silica aerogel felt of the present application forms an additional cross-linked network through the cross-linking of olefin groups, and a silica aerogel felt with good mechanical properties can be prepared at a lower fiber content.

[0048] Optionally, the fiber content may be, but is not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or other parameters within the range of 5% to 40%.

[0049] Optionally, the content of silica aerogel may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40% or other parameters within the range of 10% to 40%.

[0050] In some embodiments, the silica aerogel is a silica aerogel powder with a mesh size of 600 to 900.

[0051] In some embodiments, the aerogel slurry further comprises 1% to 5% of a dispersant, measured by mass percentage of the aerogel slurry. By adding the dispersant, the uniformity of the aerogel slurry can be further improved, which is conducive to obtaining a silica aerogel felt with consistent overall performance.

[0052] In some embodiments, the dispersant includes polyvinylpyrrolidone.

[0053] In some embodiments, the organic solvent includes one or more of cyclohexane, toluene, n-hexane and isooctane.

[0054] In some embodiments, the fibers include one or more of glass fibers, ceramic fibers, and carbon fibers.

[0055] In some embodiments, the length of the fiber is 5 mm to 40 mm. Optionally, the length of the fiber can be, but is not limited to, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm or other parameters within the range of 5 mm to 40 mm.

[0056] In some embodiments, the steps of preparing the aerogel slurry include: mixing an organic solvent and a dispersant to obtain a dispersed solution;

[0057] The dispersed solution, the fiber and the silica aerogel are mixed to obtain an aerogel slurry.

[0058] In some embodiments, the step of irradiating and crosslinking the aerogel felt preform with acrylate includes: placing the aerogel felt preform in a second solution containing acrylate, soaking for 4 hours to 24 hours to obtain a pre-crosslinked aerogel felt, and irradiating and crosslinking the pre-crosslinked aerogel felt.

[0059] In some embodiments, the solvent of the second solution includes one or more of dichloromethane, toluene, propanol, n-hexane and n-heptane.

[0060] In some embodiments, the mass concentration of the acrylate is 3% to 40% in terms of mass percentage of the second solution. Optionally, the mass concentration of the acrylate in the second solution includes but is not limited to 3%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or other values ​​within the range of 3% to 40%.

[0061] The present application uses acrylate and aerogel felt preforms for radiation cross-linking, which can form an additional three-dimensional spatial network structure inside and on the surface of the aerogel felt preform, effectively improving the structural strength of the subsequently prepared silica aerogel felt, and obtaining a silica aerogel felt that is not easy to powder.

[0062] In some embodiments, the acrylate includes one or more of methyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol tetraacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene glycol dimethacrylate, and trimethylolpropane triacrylate.

[0063] The irradiation method used in this application is irradiation. Unlike photocatalysis that requires free radical polymerization reaction and cross-linking under the action of photoinitiators, the method of irradiation using high-energy rays can transmit higher energy, and thus can induce cross-linking reactions between carbon-carbon double bonds without adding photoinitiators. In addition, high-energy rays have extremely strong penetrating power. On the one hand, they can more effectively act on the internal structure of the aerogel felt preform; on the other hand, for the combination of acrylate and aerogel felt preform with more reaction sites, irradiation can produce a more thorough reaction and obtain a denser cross-linking network.

[0064] In some embodiments, the radiation source of the radiation cross-linking treatment includes at least one of a gamma ray source, an X-ray source, and an electron beam source.

[0065] In some embodiments, the radiation dose of radiation cross-linking is 80 kGy to 800 kGy. Optionally, the radiation dose includes but is not limited to 80 kGy, 100 kGy, 200 kGy, 300 kGy, 400 kGy, 500 kGy, 600 kGy, 800 kGy or other values ​​within the range of 80 kGy to 800 kGy.

[0066] In some embodiments, the method for preparing the alkenyl-containing silica aerogel comprises:

[0067] The silica wet gel is modified with a modifier and dried.

[0068] The modifier is a silane coupling agent containing an alkenyl group.

[0069] In some embodiments, the modifier is a trichlorosilane derivative containing an alkenyl group. In this embodiment, a trichlorosilane derivative with an alkenyl group as a substituent is used as a modifier, and a condensation reaction is carried out with Si-OH remaining on the surface of the silica wet gel, thereby grafting the alkenyl group into the network structure of the silica wet gel to obtain a modified silica wet gel containing unsaturated carbon-carbon double bonds. After drying, a silica aerogel rich in chemical crosslinking reaction sites can be obtained.

[0070] In some embodiments, the modifier includes one or more of vinyltrichlorosilane, 2-propenyltrichlorosilane, 2-butenyltrichlorosilane, 5-hexenyltrichlorosilane, and 7-octenyltrichlorosilane.

[0071] The present application introduces active sites for cross-linking reaction on the silica aerogel by chemically grafting silane compounds with alkenyl groups with the silicon hydroxyl groups of silica aerogel. However, the surface of the silica wet gel obtained after aging is mostly hydrophilic silicon hydroxyl groups, while the alkenyl groups are hydrophobic groups, resulting in poor compatibility between the modifier with hydrophobic groups and the sol particles, further resulting in an extended polycondensation reaction time, poor reaction efficiency, and ultimately resulting in fewer reaction sites for the modified wet gel. For this reason, the present application selects a silane coupling agent with a chlorine group to increase the rate of the polycondensation reaction and effectively improve the efficiency of the grafting reaction. At the same time, considering that when selecting a silane coupling agent with multiple alkenyl substituents, the same incompatibility problem will be faced, and the presence of steric hindrance will further hinder the reaction. For this reason, the present application selects a trichlorosilane derivative with multiple chlorine-substituted groups, and uses the characteristics of trichlorosilane derivatives with small steric hindrance and good compatibility to introduce a considerable number of carbon-carbon double bond reaction sites on the silica wet gel structure. After drying, a silica aerogel rich in chemical cross-linking reaction sites can be obtained.

[0072] In some embodiments, the preparation of the silicon dioxide wet gel comprises the following steps:

[0073] mixing a silicon source precursor, ethanol and water to form a silica sol;

[0074] The silica sol is aged and solvent replaced to form a silica wet gel.

[0075] In some embodiments, the silicon source precursor includes one or more of methyl orthosilicate, ethyl orthosilicate, butyl orthosilicate, and isopropyl orthosilicate.

[0076] In some embodiments, the silicon source precursor, ethanol and water are mixed in a molar ratio of 1: (2-4): (9-16) of the silicon source precursor, ethanol and water. Keeping the molar ratio within the above range is conducive to forming a silica sol with low shrinkage and high porosity. Optionally, the molar ratio of the silicon source precursor, ethanol and water can be, but is not limited to, 1: 2: 9, 1: 2: 12, 1: 2: 16, 1: 3: 9, 1: 3: 12, 1: 3: 16, 1: 4: 9, 1: 4: 12, 1: 4: 16 or other ratios within the range of 1: (2-4): (9-16).

[0077] In some embodiments, after mixing the silicon source precursor, ethanol and water, the pH is adjusted to 2 to 6, and hydrolyzed to form a prepolymer solution;

[0078] The pH of the prepolymer solution is adjusted to 7-10, and condensation is performed to form a silica sol.

[0079] In some embodiments, the hydrolysis time is 0.5 to 4 hours. Alternatively, the hydrolysis time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or other values ​​within the range of 0.5 hours to 4 hours.

[0080] In some embodiments, the polycondensation time is 0.5 to 4 hours. Alternatively, the polycondensation time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or other values ​​within the range of 0.5 hours to 4 hours.

[0081] After the silicon source precursor undergoes hydrolysis and condensation, a primary gel network will be constructed to form a silica sol. At this time, only a few silicon-oxygen bonds in the gel network will be connected together, and the structural strength is low. For this reason, the silica sol needs to be aged to form a silica wet gel with higher structural strength.

[0082] In some embodiments, the aging step includes placing the silica sol in an aging solution and allowing the solution to stand.

[0083] In some embodiments, the aging solution includes one or more of water, acetone, ethanol, and n-hexane.

[0084] In some embodiments, the aging solution may be an ethanol solution of ethyl orthosilicate having a mass concentration of 1% to 20%.

[0085] In some embodiments, during aging, the standing time is 6 to 72 hours. The standing aging time can be, but is not limited to, 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, 48 ​​hours, 54 hours, 60 hours, 66 hours, 72 hours, or other values ​​within the range of 6 hours to 72 hours.

[0086] In some embodiments, during aging, the static temperature is maintained at 25° C. to 70° C. The static aging temperature can be, but is not limited to, 25° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C. or other values ​​within the range of 25° C. to 70° C.

[0087] During aging, when the system temperature is low, the molecular kinetic energy in the system is relatively low, the molecular motion is relatively stable, the hydrolysis and polycondensation reactions slow down, and the degree of crosslinking of the obtained silica wet gel is low. When the temperature is too high, the hydrolysis and condensation reaction rates will be too fast, which will easily lead to the volume shrinkage of the wet gel. In the temperature range of 25℃~70℃, it is conducive to obtaining silica wet gel with high structural strength.

[0088] The structure of the aged silica wet gel preform contains a large amount of water. The surface tension of water is large, and the stress during drying is large, which can easily affect the skeleton structure of the silica aerogel. Therefore, it is necessary to use a solvent with low surface tension to perform solvent replacement to remove the residual water inside the gel.

[0089] In some embodiments, the step of solvent replacement comprises:

[0090] immersing the silicon dioxide wet gel preform in a replacement solvent and allowing it to stand or stir;

[0091] Repeat the above steps 0 to 6 times.

[0092] Wherein, the replacement solvent includes one or more of n-hexane, cyclohexane, n-heptane and acetone.

[0093] During the solvent replacement, the water in the wet silica gel will be exchanged with the organic solvent. It can be understood that repeating the above operation means: repeating the steps of immersing the wet silica gel in the organic solvent and letting it stand. When the number of repeated operations is 0, it means that no repeated operation is performed.

[0094] In some embodiments, during solvent replacement, the volume ratio of the wet silica gel to the replacement solvent is 1:1 to 1:4. The volume ratio of the wet silica gel to the organic solvent can be, but is not limited to, 1:1, 1:2, 1:3, 1:4 or other values ​​within the range of 1:1 to 1:4.

[0095] In some embodiments, the temperature of the solvent replacement is 25° C. to 60° C. The temperature of the solvent replacement can be, but is not limited to, 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C. or other values ​​within the range of 25° C. to 60° C.

[0096] In some embodiments, the standing time of the solvent replacement is 1 h to 12 h. The standing time can be but is not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or other values ​​within the range of 1 h to 12 h.

[0097] In some embodiments, the modified wet gel is washed with a washing solvent, which includes one or more of isopropanol, propanol, n-hexane, and n-heptane.

[0098] In some embodiments, the volume ratio of the cleaning solvent to the modified wet gel is 0.5: 1 to 3: 1. The soaking time for each cleaning is 2 hours to 24 hours, and the cleaning is repeated 2 to 5 times.

[0099] In some embodiments, the drying method includes atmospheric pressure drying, supercritical drying or freeze drying. Through the drying step, the liquid phase inside the wet gel can be replaced by a gas phase to obtain a silica aerogel.

[0100] In another embodiment of the present application, a silica aerogel felt is provided, which is prepared by the above-mentioned preparation method of the silica aerogel felt.

[0101] The present application is further described in detail below in conjunction with specific embodiments.

[0102] In the following specific embodiments and comparative examples, the raw materials used, unless otherwise specified, are all commercially available products; the instruments used, unless otherwise specified, are all commercially available products; and the processes used, unless otherwise specified, are all routinely selected by those skilled in the art.

[0103] Example 1

[0104] This embodiment provides a silica aerogel felt.

[0105] The preparation method of silica aerogel felt is:

[0106] Weigh 45% of n-hexane, 5% of polyvinyl pyrrolidone, 35% of 800-mesh silica aerogel and 15% of 5 mm long ceramic fiber according to the weight ratio for use. Put n-hexane into a disperser, add polyvinyl pyrrolidone, and stir evenly at a speed of 2000 rad / min for 2 hours. Subsequently, add ceramic fiber and silica aerogel, continue stirring for 4 hours, and obtain aerogel slurry. Pour the prepared slurry into the membrane cavity, press it into a plate by an air press, and obtain an aerogel felt preform. Soak the aerogel felt preform in an ethanol solution containing 25wt% methyl acrylate for 24 hours to obtain a pre-crosslinked aerogel felt. Use an electron accelerator to irradiate and crosslink the pre-crosslinked aerogel felt, and obtain a silica aerogel felt after normal pressure drying. Among them, the drying conditions are drying at 60°C for 24 hours and then drying at 120°C for 4 hours; the irradiation source is an electron beam source, and the irradiation dose is 300kGy.

[0107] Wherein, the preparation method of silica aerogel powder is as follows:

[0108] Mix tetraethyl orthosilicate, ethanol and water in a molar ratio of 1:4:12, adjust the pH to 3 with hydrochloric acid, and hydrolyze for 1h. Use ammonia water to adjust the pH to 8, condense for 1h to obtain silica sol. The silica sol is placed in a 10wt% ethanol solution of tetraethyl orthosilicate and aged for 48h. The aged silica sol is placed in an ethanol solvent, and the solvent is replaced at room temperature, stirred for 12h, and repeated 4 times to obtain a wet silica gel. At 30°C, the wet silica gel is placed in a 25wt% ethanol solution of vinyltrichlorosilane for hydrophobic modification, and immersed for 36h to obtain a modified wet gel. Use an equal volume of ethanol to wash 4 times, the immersion time for each wash is 24h, and the silica aerogel is obtained after drying. Among them, the drying conditions are: drying at 60°C for 24h, and then drying at 120°C for 4h.

[0109] Example 2

[0110] This embodiment provides a silica aerogel felt.

[0111] The silica aerogel felt of this embodiment is different from that of Embodiment 1 in that, in terms of mass percentage, the aerogel slurry is composed of 45% toluene, 5% dispersant, 25% silica aerogel, and 25% ceramic fibers with a length of 5 mm.

[0112] Example 3

[0113] This embodiment provides a silica aerogel felt.

[0114] The silica aerogel felt of this embodiment is different from that of Embodiment 1 in that, in terms of mass percentage, the aerogel slurry is composed of 45% cyclohexane, 5% dispersant, 15% silica aerogel, and 35% ceramic fibers with a length of 5 mm.

[0115] Comparative Example 1

[0116] This comparative example provides a silica aerogel felt.

[0117] The silica aerogel felt in this comparative example is different from that in Example 1 in that the silica aerogel does not contain olefin groups.

[0118] Comparative Example 2

[0119] This comparative example provides a silica aerogel felt.

[0120] The silica aerogel felt of this comparative example is different from that of Example 1 in that: after the aerogel felt preform is formed, constant pressure drying is directly performed to obtain the silica aerogel felt.

[0121] Comparative Example 3

[0122] This comparative example provides a silica aerogel felt.

[0123] The silica aerogel felt in this comparative example is different from that in Example 1 in that:

[0124] Test Case

[0125] The performance of the silica aerogels of the above examples and comparative examples was tested, and the test results are shown in Table 1.

[0126] Powder loss rate: The silica aerogel was placed on a vibrating shaker and vibrated for 10 minutes. The relative percentage of the mass difference before and after vibration to the mass before vibration was recorded as the powder loss rate of the silica aerogel.

[0127] Bending times: Fold the silica aerogel 90° along the long axis and restore it within 3 seconds, and observe whether there are cracks or breaks at the folded part. If cracks or breaks occur, the last folding number will be recorded as the bending times of the silica aerogel, and the maximum number of folds is 50.

[0128] Thermal conductivity: The thermal conductivity of silica aerogel was tested according to the method of GB / T34336-2017.

[0129] Table 1

[0130]

[0131] As can be seen from Table 1, the silica aerogel felt of Comparative Example 1, which is cross-linked only by acrylate itself, or Comparative Example 2, which is not cross-linked, exhibits a high powder loss rate and poor flexibility in the bending test. At the same time, the silica aerogel felts of Examples 1 to 4 have a low powder loss rate and good flexibility, indicating that the powder loss performance of the silica aerogel felt can be effectively improved by co-irradiation cross-linking between silica aerogel and acrylate.

[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0133] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims, and the description may be used to interpret the content of the claims.

Claims

1. A method for preparing a silica aerogel felt, characterized in that: The steps include: obtaining an aerogel slurry containing silica aerogel and fibers; Pressing the aerogel slurry to form an aerogel felt preform; The aerogel felt preform is mixed with acrylate, irradiated and cross-linked together, and dried to form a silica aerogel felt; Wherein, the silica aerogel contains alkenyl groups.

2. The method for preparing the silica aerogel felt according to claim 1, characterized in that: In terms of mass percentage, the aerogel slurry comprises: Organic solvent 40%~80%, Silica aerogel 10%~40%, and Fiber 5%~40%.

3. The method for preparing the silica aerogel felt according to claim 2, characterized in that: The aerogel slurry further comprises 1% to 5% of a dispersant, based on the mass percentage of the aerogel slurry.

4. The method for preparing the silica aerogel felt according to claim 2, characterized in that: The fibers include one or more of glass fibers, ceramic fibers and carbon fibers; and / or The organic solvent includes one or more of cyclohexane, toluene, n-hexane and isooctane.

5. The method for preparing the silica aerogel felt according to claim 1, characterized in that: The radiation dose of the radiation cross-linking is 80 kGy to 800 kGy.

6. The method for preparing the silica aerogel felt according to claim 1, characterized in that: The acrylic acid ester includes one or more of methyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol tetraacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene glycol dimethacrylate and trimethylolpropane triacrylate.

7. The method for preparing a silica aerogel felt according to any one of claims 1 to 6, characterized in that: The preparation method of the silica aerogel comprises: The wet silica gel is hydrophobically modified using a modifier and dried; The modifier is a silane coupling agent containing an alkenyl group.

8. The method for preparing the silica aerogel felt according to claim 7, characterized in that: The modifier includes one or more of vinyl trichlorosilane, 2-propylene trichlorosilane, 2-butenyl trichlorosilane, 5-hexenyl trichlorosilane and 7-octenyl trichlorosilane.

9. A silica aerogel felt, characterized in that: The silica aerogel felt is prepared by the preparation method of any one of claims 1 to 8.

10. A thermal insulation material, characterized in that: The thermal insulation material comprises the silica aerogel felt described in claim 9.